Answer:
The answer will be listed below.
Explanation:
Since there is an x= 2y+3, you can plug that equation into x in the equation 2x-3y=7. You must find y first.
2(2y+3)-3y=7
Now distribute 2 and you will get 4y+6-3y=7.
Combine 4y and -3y and have an equation of y+6=7.
Subtract 6 to both sides and you will have an answer of y=1
Now since you found y, now find x. To find x, substitue y=1 into any equation listed (you'll get the same answer anyways). Let's use x=2y+3 as an example. Substitute the 1 for y.
x=2(1)+3
Now you have x=2+3, which is 5.
x=5 and y=1.
To make sure this is correct, plug both the numbers into an equation, let's use the first one now.
2(5)-3(1)=7
7=7
In the end, the euqtaion equals 7, which means the answer is correct.